Răspuns :
Răspuns:
Explicație pas cu pas:
A(a;2) si B(3;a-1) si AB=2√2
AB²=(xb-xa)²+(yb-ya)² unde x si y sunt coordonatele punctelor
8=(3-a)²+(a-1-2)²
8=9-6a+a²+a²-6a+9
8=2(a-3)²
4=(a-3)² ⇒Ia-3I=2
a-3=2 ⇒a=5
a-3=-2 ⇒a=1
Răspuns:
Explicație pas cu pas:
(a - 3)^2 + (2 - a + 1)^2 = (a - 3)^2 + (3 - a)^2 = a^2 - 6a + 9 + 9 - 6a + a^2
= 2a^2 - 12a + 18
AB = √2a^2 - 12a + 18 = 2√2
2a^2 - 12a + 18 = 8
2a^2 - 12a + 18 - 8 = 0
2a^2 - 12a + 10 = 0
a^2 - 6a + 5 = 0
Δ = 36 - 20 = 16
a1 = (6 + 4)/2 = 5
a2 = (6 - 4)/2 = 1
pentru a1 = 1; 2a^2 - 12a + 18 = 2 - 12 + 18 = 8 > 0
pentru a2 = 5; 2a^2 - 12a + 18 = 50 - 60 + 18 = 8 > 0
a = {1; 5}